Leaving, Staying in and Returning to the Hometown - Janna Albrecht; Joachim Scheiner (Raumforschung und Raumordnung, 2022)
Couples' residential decisions are based on a large variety of factors including housing preferences, family and other social ties, socialisation and residential biography (e.g. earlier experience in the life course) and environmental factors (e.g. housing market, labour market). This study examines, firstly, to what extent people stay in, return to or leave their hometown (referred to as ‘migration type’). We refer to the hometown as the place where most of childhood and adolescence is spent. Secondly, we study which conditions shape a person’s migration type. We mainly focus on variables capturing elements of the residential biography and both partners’ family ties and family socialisation. We focus on the residential choices made at the time of family formation, i.e. when the first child is born. We employ multinomial regression modelling and cross-tabulations, based on two generations in a sample of families who mostly live in the wider Ruhr area, born around 1931 (parents) and 1957 (adult children). We find that migration type is significantly affected by a combination of both partners' place of origin, both partners' parents' places of residence, the number of previous moves, level of education and hometown population size. We conclude that complex patterns of experience made over the life course, socialisation and gendered patterns are at work. These mechanisms should be kept in mind when policymakers develop strategies to attract (return) migrants.